(untitled) (London Journal of Medical and Health Research, 2025)
Renal cell carcinoma, (RCC) the most prevalent of kidney cancers, is a relatively common cancer, constituting approximately 10% of all cancers in adults. Many molecular subtypes have been characterized for RCC, the most common being clear cell RCC, or ccRCC, which occurs in close to 75% of cases, and has a strong association with mutations in the von Hippel-Lindau (VHL) tumor suppressor gene [1]. ccRCC constitutes close to 80% of metastatic presentations. Histology shows acinar growth and clear cell cytology, surrounded by a rich vasculature. Having a strong association with mutations in the von Hippel-Lindau tumor suppressor gene, ccRCC exhibits loss of VHL gene by 3p chromosomal loss at the 3p25 locus. Another histologic subtype includes non clear cell renal cell carcinoma nccRCC. Somatic ccRCC is characterized by inactivation of the protein products of VHL (pVHL), which promotes transcription of genes implicated in tumor formation and growth [1]. Localized and systemic therapies differ on the basis of clinical presentation such as primary or metastatic disease, and they can be administered in first-line or adjuvant settings. Before the advent of precision medicine, renal cell carcinoma was treated with non-specific immunomodulatory agent such as cytokines [2]. IL-2 and high-dose interferon-alpha (HD IFN-alpha) were considered the treatment of choice for renal cell carcinoma due to the cancers predisposition for lack of sensitivity to chemotherapy and hormonal therapy, however response was variable, with varying optimal effects and occurrence of toxicity. These treatments have been questioned due to data demonstrating that when these agents are administered in combination with VEGF targets, and they have shown less than ideal efficacy. Patients progressed on disease and were required to be followed up with systemic VEGFR targets in second line settings.